New functions and signaling mechanisms for the class of adhesion G protein–coupled receptors. (25th November 2014) - Liebscher, Ines; Ackley, Brian; Araç, Demet; Ariestanti, Donna M.; Aust, Gabriela; Bae, Byoung‐il; Bista, Bigyan R.; Bridges, James P.; Duman, Joseph G.; Engel, Felix B.; Giera, Stefanie; Goffinet, André M.; et al.
Abstract : The class of adhesion G protein–coupled receptors (aGPCRs), with 33 human homologs, is the second largest family of GPCRs. In addition to a seven‐transmembrane α‐helix—a structural feature of all GPCRs—the class of aGPCRs is characterized by the presence of a large N‐terminal extracellular region. In addition, all aGPCRs but one (GPR123) contain a GPCR autoproteolysis–inducing (GAIN) domain that mediates autoproteolytic cleavage at the GPCR autoproteolysis site motif to generate N‐ and a C‐terminal fragments (NTF and CTF, respectively) during protein maturation. Subsequently, the NTF and CTF are associated noncovalently as a heterodimer at the plasma membrane. While the biological function of the GAIN domain–mediated autocleavage is not fully understood, mounting evidence suggests that the NTF and CTF possess distinct biological activities in addition to their function as a receptor unit. We discuss recent advances in understanding the biological functions, signaling mechanisms, and disease associations of the aGPCRs.